Analisis Pengaruh Kualitas Pelayanan Dan Word Of Mouth Terhadap Keputusan Pembelian Mie Ayam Arjuna Di Randudongkal Pemalang - Tata Aulia Rahma,; Khalid Iskandar,; Muhammad Syaifulloh, (Manajemen Kreatif Jurnal, 2023)
This study was set behind a decrease in the sales of arjuna chicken noodles during 2020-2021. This decline in sales indicates a decrease in consumer buying decisions for arjuna chicken noodle products so that it can be formulated in this study that how consumers make decisions to buy arjuna chicken noodle amid a growing competitive phenomenon based on service quality and word of mouth. The purpose of this study was to analyze the effect of service quality and word of mouth on the purchase decision of arjuna chicken noodles. This study uses quantitative methods. Data collected using questionnaire and interview techniques. The respondents in this study were 50 people who met one of the five criteria; decision-making, purchasing, consuming chicken arjuna noodles at Randudongkal Pemalang. Three hypotheses were formulated and tested using regression analysis. Research results show that service quality does not have a significant effect on purchasing decisions, while Word Of Mouth has a significant effect on purchasing decisions. Word of mouth also had a high effect on purchasing decisions on Arjuna Chicken Mie Randudongkal Pemalang.